Morphological computed tomography features of surgically resectable pulmonary squamous cell carcinomas: Impact on prognosis and comparison with adenocarcinomas - Koenigkam-Santos, Marcel; Warth, Arne; Schlemmer, Heinz-Peter; Kauczor, Hans-Ulrich; Heußel, Claus Peter; Puderbach, Michael (European journal of radiology, 2014)
Objective - To characterize the morphological computed tomography (CT) features of pulmonary squamous cell carcinomas (SQCC) submitted to therapeutic resection; to correlate these features with patients’ outcomes; and to compare with pulmonary adenocarcinomas (ADC). - Materials and methods - Two chest radiologists retrospectively evaluated CT exams of 123 patients with SQCC resected between 2002 and 2008. Tumors’ size, location (central vs. peripheral), shape, margins, attenuation, enhancement, presence of calcification, cavitation, internal air bronchograms and pleural tags were assigned by consensus. Prevalence of features was compared with patients’ survival data and a previously studied population of ADC surgically resected at the same time period. - Results - Cavitation correlated negatively with overall (hazard ratio=3.04), disease-specific (HR=3.67) and disease-free survival (HR=2.69), independent from age, gender, tumor pathological stage, size, and location. In relation to ADC, SQCC presented different shape, margins, attenuation, enhancement, with more cavitation, rare internal air bronchograms, and less pleural tags. Differences were also significant when comparing only the peripheral type of tumors. - Conclusions - Cavitation at CT was an independent and negative predictive factor for SQCC. Different CT morphological features were described for SQCC and ADC. Image evaluation of lung lesions should go beyond measuring and addressing adjacent structures invasion. Adequate imaging characterization not only helps to differentiate benign versus malignant disease and to determine malignancy staging, it may also imply the histologic subtype and improve the prognostic assessment of lung cancer patients.